DESAIN DIDAKTIS PEMBELAJARAN OPERASI HITUNG BILANGAN BULAT BERBASIS PERMAINAN TRADISIONAL BOLA BEKEL DI SEKOLAH DASAR - Nadia Adillah Harpizon; Mhmd Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT This paper is motivated by the results of research that the concept of addition, subtraction, multiplication and division is one of the integer counting operations that makes students experience learning obstacles in solving problems related to the material. The purpose of this research is to obtain a description of the didactic design of the concept of integer counting operations based on the study of Learning Obstacle. In connection with these problems, there is a need for alternative learning to make it easier for students to understand the concept of integer operations. One of the alternative learning designs used is by applying the Didactical Design Research approach accompanied by the use of the traditional game Bola Bekel. It can be seen that by using this ball bekel game, students are easier in understanding integer counting operations. The research method used is qualitative research with the Didactical Design Research (DDR) model. The research subjects were first grade students. The research instruments used were observation, interview, and documentation. Based on the results of the study that students' understanding in performing whole number counting operations can be achieved.